Emotions, Social Policies and Public Responsibilities: a Contribution to Social Innovation - Giacomini, Gabriele (Scenari, 2021)
The new psychology of decision-making and the sciences of happiness demonstrate that individuals are not merely rational, as is largely assumed in the classical social sciences: they also possess irrational and emotional characteristics which are not negligible. Therefore, cognitive and experimental sciences offer contributions for the development of innovative public policies based upon a psychological description of individuals that is now becoming less abstract and more realistic. From cognitive nudges to a national income accounting that takes into account the wellbeing of citizens in the most complete manner possible, there are a variety of innovative instruments at the disposal of public decision-makers. However, the cognitive and social paradigms present us with some questions regarding the ethical/political responsibilities of public decision-makers: is it right and desirable for public decision-makers to use the irrationality and emotions of citizens to pursue specific objectives? Are they indeed able to and interested in using the instruments they have been provided with by the new cognitive and decision-making sciences?